Histopathological Studies of Experimentally Infected Shing, Heteropneustes fossiliswith Aeromonas hydrophila Bacteria (Progressive Agriculture, 2013)
Heteropneustes fossilis (shing) of 35g body weight were experimentally infected with Aeromonas hydrophila by two different methods: viz. intraperitonial and intramuscular injection. A standard dose of infection (6.4 × 107 CFU/ml) was selected based on predetermined LD50. Each method gave rise to the mortality of shing up to 85%. Clinical signs of fish included injury, hemorrhage and large ulcerative lesions on the body at the injected area. In kidney, liver and intestine pathologically, massive atrophy and focal necrosis were found. Hemorrhage, Vacuolation and atrophy of hepatic sinusoids represented by necrosis of the sinusoidal lining cells, degeneration of hepatic tissue and distribution of bacterial cell all over the tissue were found in liver. Atrophy, hemorrhage, villi missing and missing of epithelium were found in intestine of the experimentally infected shing. Bacterial cells were distributed in the whole hematopoietic tissue including the renal tubules. Tissue abscess characterized by focal necrosis, hemorrhage and Vacuolation were also found in the kidney of the infected shing. But the above symptoms were not found in the organs of the apparently healthy shing species.DOI: http://dx.doi.org/10.3329/pa.v19i1.17359 Progress. Agric. 19(1): 89 - 96, 2008